Environmental Assessment of Polycyclic Aromatic Hydrocarbon Concentrations in Atmospheric Air at Daura Refinery - A.A.Shanshal, Muthna; H. Afaj, Adnan; H. Almousawi, Israa M. (Iraqi Journal of Science, 2023)
Polycyclic aromatic hydrocarbons (PAHs) were measured in aerosol from air samples, which collected for the period from April 2012 to February 2013, in Baghdad city, at Daura Refinery. Aerosol samples were collected on cellulose fiber filters for 1.5 h in each site for the morning and evening time. These aerosol samples undergone soxhlet extraction.After the extraction, 49 samples were analyzed by GC-MS in order to determin 16 PAH compounds. The parameters temperature, relative humidity and wind speed were measured during the measurement period. The PAH concentrations were different for location inside and outside Daura refinery. Naphthalene was the most abundant PAH detected in all points at the site sampling for all seasons. There is strong correlation between total suspended particles (TSP) and total polycyclic aromatic hydrocarbons (TPAH) (0.897, 0.966, 0.800) for spring, summer and autumn respectively. There was positive correlation between the total PAH concentrations and the relative humidity in the spring, autumn and winter seasons.